2011
DOI: 10.1093/logcom/exr039
|View full text |Cite
|
Sign up to set email alerts
|

Arc consistency and friends

Abstract: A natural and established way to restrict the constraint satisfaction problem is to fix the relations that can be used to pose constraints; such a family of relations is called a constraint language. In this article, we study arc consistency, a heavily investigated inference method, and three extensions thereof from the perspective of constraint languages. We conduct a comparison of the studied methods on the basis of which constraint languages they solve, and we present new polynomial-time tractability result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…A different weakening of (2, 3)-minimality is singleton arc consistency (see [12]). An instance is singleton arc consistent if it is 1-minimal and the 1-minimality algorithm succeeds even when we add any constraint of the form "x = a", where x is a variable and a ∈ P x .…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…A different weakening of (2, 3)-minimality is singleton arc consistency (see [12]). An instance is singleton arc consistent if it is 1-minimal and the 1-minimality algorithm succeeds even when we add any constraint of the form "x = a", where x is a variable and a ∈ P x .…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…An instance is singleton arc consistent if it is 1-minimal and the 1-minimality algorithm succeeds even when we add any constraint of the form "x = a", where x is a variable and a ∈ P x . The authors in [12] ask whether any singleton arc consistent instance over a bounded width language has a solution. A positive answer would give a more efficient algorithm for solving CSPs over bounded width languages.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…∧ α n ), where the x i are variables and where the α i are atomic formulas. These sentences have been approached by researchers possessing a variety of motivations and perspectives [29,32,40,39,34,35,36,9,16,3,4,5,19,18,23,26,25]. In the database literature, they are known as conjunctive queries and are of central interest; the problem of model checking such sentences is also a formulation of the constraint satisfaction problem [40].…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…Connected row-convex constraints [77] are closed under the ternary median operation which is another example of a majority operation [111]. It has been recently shown that singleton arc-consistency solves CSP( ) when admits a majority polymorphism [40].…”
Section: Language Classes Solved By Local Consistencymentioning
confidence: 99%